A model for the integrated and transversal monitoring and evaluation of rural development programmes implemented by the Limpopo Provincial Government in South Africa - Olivier, N.J.J. (Nicolaas Johannes Jacobus) (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2015.